Estrutura Cognitiva para Tecnologias Educacionais Construtivistas ECoTEC e seu Instrumento de Otimização Web-ECoTEC - Santos, Eliane Elias Ferreira dos (2009)
This research developed a method of evaluation for computer tools for education (FCE), called Structure Cognitive for Education Technologies Constructivists (ECoTEC). This methodology detects the construction of structures of logical-mathematical thinking through the proposed activities on FCE. In the ECoTEC conception was used a strategy of analysis which includes: organization of cognitive structure of logical-mathematical thinking according to Piaget operative theory; the differentiation of essential concepts of this theory; and the deconstruction of Piaget operative theory. It was made an ascendant unfolding of principal concepts and organized them in a sort of integrated network and additional. The structure allows comprehending the structures of thinking in the concrete operative periods and formal operative, according to the operative activities, the interaction and the cooperation. From this structure it was established a process of measurement. It was used as a strategy for development the paradigm GQM (Goal/Question/Metric), a technique for identification of significant metrics. To automate the collection for information to the user and assist in calculation of the metrics for the characterization of FCE was developed an instrument of optimization called Web-ECoTEC. The validation of Web-ECoTEC while methodology of evaluation of FCE revealed his potentiality to characterize these tools according to the structure of thinking developed. The evaluations generated by the methodology can guide teachers, educators and educational professionals in the selection of FCE, since that these evaluations showed the structures of logical-mathematical thinking which can be used with the FCE evaluated. The utilization of Web-ECoTEC for validation, also presented efficient in the collection of answers and in generation of results of characterization of FCE.